2009
DOI: 10.2224/sbp.2009.37.5.661
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Attitudes Towards the Budgetary Process on Attitudes Towards Budgetary Slack and Behaviors to Create Budgetary Slack

Abstract: In this study more positive attitudes towards the budgetary process are examined to see whether or not these cause less favorable attitudes towards budgetary slack, and whether less favorable attitudes towards budgetary slack causes or are caused by behaviors intended to create budgetary slack. The effects are tested using a structural equation model based on questionnaire data gained from 216 Taiwanese managers. The results indicate that more positive attitudes towards the budgetary process result in attitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 0 publications
1
10
0
1
Order By: Relevance
“…Stevens (2002) found that ethical and reputational concerns might influence budgetary slack creation. Huang and Chen (2009, p. 669) investigated the effect of managers’ attitudes towards the budget process and creation of slack on the incidence of budgetary slack, describing this behaviour as “underhanded and devious tactics”. With few exceptions, the language used in this stream of research has remained stuck in the negative paradigm, which influenced our own small‐scale study.…”
Section: Introductionmentioning
confidence: 99%
“…Stevens (2002) found that ethical and reputational concerns might influence budgetary slack creation. Huang and Chen (2009, p. 669) investigated the effect of managers’ attitudes towards the budget process and creation of slack on the incidence of budgetary slack, describing this behaviour as “underhanded and devious tactics”. With few exceptions, the language used in this stream of research has remained stuck in the negative paradigm, which influenced our own small‐scale study.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Mia (1987) revealed that participative budgeting fosters a positive attitude toward jobs. Additionally, Huang and Chen (2009) indicated that a more favourable attitude toward the budgeting process is positively correlated with a more favourable attitude toward budgetary slack, and as such, it leads to the reduction of the creation of budgetary slack. In line with the mentioned studies, the results of this study prove that when the managers participate more in the budgeting process, their attitude toward the budget attained is positive and as such, this leads to the reduction of the creation of budgetary slack.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, this study contributes to the budgeting literature by implying the inclusion of the theory of planned behaviour to explain the significant relationship between the managers' attitude toward the budget attained and their creation of budgetary slack. Although prior budgeting studies have realised the crucial role of the managers' attitude related to their creation of budgetary slack (Huang & Chen 2009;Huang & Chen 2010;Wentzel 2004), very little research has recognised the potential of this theory in explaining this relationship. By extending the knowledge on the theory of planned behaviour as related to budgeting research, this study sheds lights on the psychological mechanism underlying the relationship between the managers' attitude and their creation of budgetary slack.…”
Section: Discussionmentioning
confidence: 99%
“…Penganggaran melibatkan bawahan untuk menetapkan dan mencapai target anggaran serta atasan sebagai pihak yang mengalokasikan sumber daya tersebut (Huang dan Chen 2009). Persiapan dan pelaksanaan dalam proses penganggaran dapat memberikan dampak yang signifikan pada sikap, perilaku, dan kinerja pihak-pihak yang terlibat didalamnya (Yuen 2004).…”
Section: Latar Belakangunclassified